2021
DOI: 10.21037/apm-21-345
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of psychological intervention on perioperative anxiety and depression of patients with severe blepharoptosis undergoing autologous fascia lata frontal muscle suspension

Abstract: Background: Perioperative negative emotion of surgical patients has a greater impact on surgical efficacy and prognosis. The study aimed to analyze the effect of psychological intervention on perioperative anxiety and depression of patients with severe blepharoptosis undergoing autologous fascia lata frontal muscle suspension, and provide a reference for improving and optimizing patient care plans.Methods: Ninety-two patients with severe blepharoptosis who underwent autologous fascia lata frontal muscle suspen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…In addition, after becoming familiar with the procedure and expected results, it can also alleviate the fear and anxiety before and after the surgery. [23][24][25][26] The results of this study showed that after the intervention, compared with the control group, the study group had reduced levels of tension, fatigue, confusion, anger, depression, and POMS index, while energy and self-esteem scores increased (P < .05). This suggests that preoperative nursing visits combined with anticipatory nursing can have a positive impact on patients' psychological state.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In addition, after becoming familiar with the procedure and expected results, it can also alleviate the fear and anxiety before and after the surgery. [23][24][25][26] The results of this study showed that after the intervention, compared with the control group, the study group had reduced levels of tension, fatigue, confusion, anger, depression, and POMS index, while energy and self-esteem scores increased (P < .05). This suggests that preoperative nursing visits combined with anticipatory nursing can have a positive impact on patients' psychological state.…”
Section: Discussionmentioning
confidence: 73%
“…In addition, after becoming familiar with the procedure and expected results, it can also alleviate the fear and anxiety before and after the surgery. [23–26]…”
Section: Discussionmentioning
confidence: 99%
“…When the patient has misunderstandings about the disease or treatment, it can not only affect the treatment compliance and treatment effect, but also easily cause psychological imbalance, leading to a series of bad emotions such as anxiety, depression, worry, resistance, etc., which in turn can also affect the patient's compliance and effect with treatment ( 20 ). After care in this study, SAS and SDS scores were lower in both groups than before care, and were lower in the joint group than in the regular group; After care, the joint group was more satisfied with care than the regular group ( P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…(8,37) El rol de enfermería desempeña un papel fundamental dentro de la atención de salud, ya que la misma permitirá brindar un alivio de los síntomas que anteriormente fueron mencionados por medio de una comunicación afectiva y siendo empáticos con los mismos, (38) haciendo que la paciente logre aumentar su nivel de autoeficiencia y esperanza, por ende, es necesario que se mantenga la relación profesional de saludpaciente, al igual que generar un entorno de confianza y respeto mutuo. (39) El personal de enfermería con el transcurso del tiempo ha ido evolucionando en cuanto a los cuidados enfocados al paciente principalmente en el postoperatorio inmediato que comprende las primeras 24 horas después de la intervención quirúrgica, en donde se puede identificar complicaciones, mediante la valoración de la respuesta al procedimiento realizado. (7) Este periodo es el más importante dado que es el momento en donde los pacientes recuperan su estado de conciencia.…”
Section: Discussionunclassified